The Effects Of Fan Activity And Views On Purchase Decision In The Genshin Impact Fanwork Market: a Literature Synthesis - Nathania, Gabriella Callista Firsty; Aprilianty, Fitri (Integrasi Sains Media, 2023)
Since the beginning of the industry, role-playing games (RPGs) have been among the most widely played game categories. As one of the worldwide top-grossing role-playing games in 2022, Genshin Impact is currently the 4th most popular game In Indonesia. With this popularity, many commercialized Genshin Impact fanworks circulated daily in the fan community, more popularly known as fandom. However, not all fanworks are accepted in the fandom and are considered